The Northern Ireland census of population and housing: looking back and looking forward - Caven, Norman; Evans, Trevor; Beatty, Robert (Statistical and Social Inquiry Society of Ireland, 1998)
A census of population and housing, even in a country as small as Northern Ireland, is a major undertaking and much time, effort and resources are devoted to it. At a national level it is the largest single statistical exercise carried out by government - indeed at one stage during the 1991 census around 150,000 people were employed on it in the United Kingdom as a whole. Data collected in a census have many uses - foremost perhaps being the provision of an accurate population count at local level. In addition, the rich detail of census data provides essential information to plan and deliver services to the population as a whole and various subgroups within it, including those most in need.
Read before the Society, 12 March 1998
Keywords: Census data; Northern Ireland demographics; Northern Ireland Statistics and Research Agency; Population; 314.15